PENGARUH DIMENSI KUALITAS JASA PADA KEPUASAAN KONSUMEN PADA RESTORAN MAKANAN CEPAT SAJI - Elisabet Dita Septiari (Universitas Ahmad Dahlan, 2016)
This study was conducted to analyze the effect of service quality dimensions toward customer satisfaction. Not all of these dimensions have same impact toward customer satisfaction in different service companies. A quantitative method was employed in this research. The respondents were customers of fast food restaurant. This study successfully collected the data with purposive sampling and analyzed 110 samples using multiple regressions. There were two fi nding, the fi rst all of the service quality dimensions simultantly impacted customer satisfaction. Second, only tangibles, reliability, and assurance have positive effect toward customer satisfaction. This study gives insight to marketer or manager in service companies to be aware with dimension of service quality dimensions. They must analyze which dimensions that have impact on their customer satisfaction.